Responses of various types of antennas to the globally distributed air-earth current monitored at Maitri, Antarctica - Jeeva, K.; Seemala, Gopi K.; Selvaraj, C.; Rathod, Gopalsingh; Kamra, A.K.; Sinha, A.K. (My University, 2021)
The role of antennas in the detection of atmospheric conduction current has been discussed since the beginning of the 20th century. Propriety of the antenna design needs to be reviewed from time to time as the measurements experience different problems on various terrains. The present work deals with such issues and brings out a suitable antenna design to detect the conduction current observed at the Indian Scientific Research Station at Maitri (70.8°S 11.7°E), Antarctica. Two long wire antennas and two plate antennas are simultaneously used to monitor the air-Earth current in the open space at this station. The experiments reveal that the currents recorded by the long-wire antenna and plate antenna display similar characteristics but differ in the magnitude and the response to the varying current. On a fair-weather day the mean current density obtained by 41 m long-wire antenna is ~0.4 pA m−2, 10 m long-wire antenna is 2.5 pA m−2, 0.25 m2 plate antenna is 3.5 pA m−2, and 1 m2 plate antenna is 4.2 pA m−2. The current sensed by 1 s and 1000 s R–C time constant do not show any significant difference in the hourly mean diurnal variation as well as in the magnitude. The study reveals that a plate antenna is a better option for the long term monitoring of air-Earth current. The simultaneously monitored potential gradient at this station and Vostok (78.4° S, 106.8° E) are used to identify the local and global electric signals.
Keywords: Long wire antenna; Plate antenna; Effective area; Physical area; R–C Time constant